Food Habits and Volume of Training in Chilean Paralympic Athletes [Hábitos Alimentarios y Volumen de Entrenamiento en Atletas Paralímpicos Chilenos] - Herrera-Valenzuela, T (Sociedad espanola de dietetica, 2016)
Introduction: It is important that athletes present good eating habits and adequate training loads to ensure adequate preparation to face the competition. Objective: To determine food consumption patterns and volume of training of Chilean Paralympians. Methods: were evaluated 27 Paralympians Chileans (29.6% women), who practiced swimming (n = 8), table tennis (n = 6), soccer 5 (n = 1), powerlifting (n = 8) and wheelchair tennis (n = 4). Data collection was obtained by two surveys: one on eating habits and another on the volume of sports training. Results: 50% of men meet the recommended intake of fruits and homemade food portions; 100% of women consume breakfast, but with low intake of fruits, fish, legumes and whole grain foods. In addition, the intake of sugary drinks is high, especially in women, and salt in men. Both men and women spend more weekly sessions to technical and tactical training (men 4,17 ± 3,03; Women 4 ± 3.67) compared to physical preparation (men 3,22 ± 3,13; 1,63 women ± 0.52); the velocity component addressed less per week (men: 0.92 ± 1.29, women: 2 ± 2.12) and flexibility the most considerate (men: 4 ± 4.59; women: 6 ± 5.89 ), although with fewer hours of training (men 1.9 ± 1.91 h.; women 2 ± 2 h.). Conclusion: Chilean Paralympians have poor eating habits and distribution of training volume that has more precision when considering working hours.